Peran sistem filsafat sebagai sumber historis, sosiologis, dan politis Pancasila - Ramadhani, Muhammad Iqbal (Maliki Interdisciplinary Journal, 2026)
Pancasila is recognized not only as the foundation of the state, but also as a fundamental philosophical system. This philosophical system provides the basis for the state's worldview, way of thinking, and policies, which are deeply rooted in the identity of the Indonesian people. This study analyzes the role of Pancasila as a philosophical system, covering its historical, sociological, and political sources, as well as identifying its dynamics, challenges, and urgency. Pancasila is an absolute unity that is singularly diverse and coherent, described in a pyramidal hierarchical unity. Its values are rooted in the long history of the archipelago as the basis of civilization and local wisdom. Politically, Pancasila was formalized as a Weltanschauung worldview by the founders of the nation, serving as a crucial ideological consensus to unite and save the country from disintegration. Over time, Pancasila has undergone significant dynamics: from the theo in the New Order era. However, it faced a decline in its existence and philosophical resonance in the Reformation era. The main global ideological challenges faced are capitalism, which threatens social justice through excessive individual freedom, and communism, which eliminates the role of the people through excessive state domination.